Complete Revascularization and Survival in STEMI. Issue 1 (29th September 2021) - Sustersic, Miha; Mrak, Miha; Svegl, Polona; Kodre, Anamarija Rebolj; Kranjec, Igor; Fras, Zlatko; Bunc, Matjaz
Background: Complete revascularization (CR) of ST-elevation myocardial infarction patients with multivessel coronary artery disease (MVD) has proven better regarding combined endpoints than incomplete revascularization (IR) in recent randomized control trials with no impact on survival. Objective: To retrospectively evaluate the impact of complete CR during the index hospitalization on survival in STEMI patients with MVD. Methods and results: We included all patients with MVD who underwent successful primary percutaneous coronary intervention for STEMI during their index hospitalization at the University Medical Centre Ljubljana, Slovenia (from 1 January 2009 to 3 April 2011). Coronary angiograms were reviewed for non-culprit coronary arteries (>2 mm in diameter and ≥50% stenosis) treated with percutaneous coronary intervention. Rates of all-cause and cardiovascular death were compared between 235 patients who underwent CR (N = 70) or IR (N = 165). After a median follow-up of 7.0 years (interquartile range 6.0–8.2) the CR group had lower rates of all-cause death (15.7% vs 35.8%, log-rank p = 0.003) and cardiovascular death (12.9% vs 23.6%, log-rank p = 0.046). Multivariable analysis with adjustment for confounders showed no benefit of CR for all-cause death (hazard ratio [HR] 0.60, 95% confidence interval [CI] 0.31–1.18, p = 0.139) or cardiovascular death (HR 0.80, 95% CI 0.37–1.72, p = 0.560). Age, elevated serum creatinine at inclusion, diabetes and cardiogenic shock at presentation were predictors of death. Conclusions: Patients with STEMI and MVD who underwent CR showed lower all-cause and cardiovascular death during follow-up than those who underwent IR. However, after adjustment for confounders, the real determinates of survival were independent of the revascularization method.